PENDIDIKAN AGAMA ISLAM DALAM ERA GLOBALISASI: MENYEIMBANGKAN TRADISI DAN MODERNITAS - Zuhri, Achmad (Universitas Islam Nahdlatul Ulama Jepara, 2024)
This article discusses how Islamic religious education can remain relevant and effective by balancing traditional values and modern approaches. The research method used is library research, involving the collection of literature data from several journal articles and books, followed by reading, noting, and processing the research material. Values such as simplicity, obedience, and togetherness remain vital in shaping students' character. Modernity and technology bring changes in teaching methods, curriculum, and access to information, which can enrich Islamic religious education if integrated correctly without sacrificing traditional values. Strategic approaches required include teacher education and training, the development of an inclusive curriculum, dialogue and collaboration among stakeholders, contextual approaches, case studies, and continuous evaluation and adjustment. Teachers need to be trained in the use of technology and have a deep understanding of Islamic teachings. An inclusive curriculum should combine religious values with 21st-century skills relevant to students' everyday lives. Collaboration among scholars, educators, technology experts, parents, and religious organizations is crucial to achieve this balance. With the right strategies, Islamic religious education can remain relevant, shape a generation with noble character and extensive knowledge, and strengthen religious identity amidst the dynamics of changing times.